Older adults’ coping strategies during the COVID-19 pandemic – a longitudinal mixed-methods study - Kastner, Lydia; Suenkel, Ulrike; Eschweiler, Gerhard W.; Dankowski, Theresa; von Thaler, Anna-Katharina; Mychajliw, Christian; Brockmann, Kathrin; Maetzler, Walter; Berg, Daniela; Fallgatter, Andreas J.; Heinzel, Sebastian; Thiel, Ansgar (Frontiers in Psychology, 2023)
Introduction Older age is a main risk factor for severe COVID-19. In 2020, a broad political debate was initiated as to what extent older adults need special protection and isolation to minimize their risk for SARS-CoV-2 infection. However, isolation might also have indirect negative psychological (e.g., loneliness, stress, fear, anxiety, depression) or physical (e.g., lack of exercise, missing medical visits) consequences depending on individual strategies and personality traits to cope longitudinally with this crisis. Methods To examine the impact of individuals’ coping with the pandemic on mental health, a large sample of 880 older adults of the prospective longitudinal cohort TREND study were surveyed six times about their individual coping strategies in the COVID-19 pandemic between May 2020 (05/2020: Mage = 72.1, SDage = 6.4, Range: 58–91 years) and November 2022 in an open response format. The relevant survey question was: “What was helpful for you to get through the last months despite the COVID-19 pandemic? E.g., phone calls, going for a walk, or others.” Results and Discussion In total, we obtained 4,561 records containing 20,578 text passages that were coded and assigned to 427 distinct categories on seven levels based on qualitative content analysis using MAXQDA. The results allow new insights into the impact of personal prerequisites (e.g., value beliefs, living conditions), the general evaluation of the pandemic (e.g., positive, irrelevant, stressful) as well as the applied coping strategies (e.g., cognitive, emotional- or problem-focused) to deal with the COVID-19 pandemic by using an adapted Lazarus stress model. Throughout the pandemic emotional-focused as well as problem-focused strategies were the main coping strategies, whereas general beliefs, general living conditions and the evaluation were mentioned less frequently.